The Comparison of Perfectionism Components among Patients with Obsessive - Compulsive, Major Depression Disorders, and Normal People - Ali Mohammadzadeh; Ali Kheiri Hiagh; Majid Vahedi (Journal of Fasa University of Medical Sciences, 2017)
Background & Objectives: Major depression and obsessive - compulsive disorders have some comorbidities. The objective of this study is to compare perfectionism and its components in patients with depression, obsessive - compulsive disorders and normal individuals.